Vegetables for sale at the K Supermarket in Rovaniemi, Finland ... - Campbell, Sandy (University of Alberta Library, 2018)
These vegetables were for sale in the city of Rovaniemi, Finland near the Arctic Circle in June 2018. Finnish grown onions cost 2.80 Euros/bunch, while Finnish grown honey turnips cost 4.00 Euros/bunch. ...